UJI TOKSISITAS HASIL FRAKSINASI EKSTRAK DAUN GANDARIA (Bouea macrophylla Griff) TERHADAP LARVA UDANG (Artemia salina Leach) DENGAN METODE BSLT (Brine Shrimp Lethality Test) - Hasmar, Wahyu Nuraini; Victoria, Michelia; Inayah, Nurul; Azizi Musdar, Tamzil; Lismayani Ilyas , Ika; Israwan Aziz , Muhammad (Journal Pharma Saintika, 2025)
Bouea macrophylla Griff (gandaria) is a rare fruit plant native to Maluku that possesses scientific potential which has not been widely explored. Its leaves contain quercetin, a flavonoid known to have antioxidant, anti-inflammatory, anticancer, antimicrobial, cardioprotective, and antidiabetic effects at non-toxic doses. This study evaluated the toxicity of leaf extract fractions in ethanol, ethyl acetate, and n-hexane solvents using the Brine Shrimp Lethality Test (BSLT) to determine the LC₅₀ value against Artemia salina larvae. The results showed that the n-hexane and ethanol fractions were toxic, with LC₅₀ values of 61.66 µg/mL and 170.61 µg/mL, respectively, while the ethyl acetate fraction exhibited much lower toxicity (LC₅₀ = 1425.61 µg/mL). This study indicates that the n-hexane and ethanol fractions have significant cytotoxic activity and therefore have the potential to inhibit cancer cell growth.